2017
DOI: 10.1002/cpt.943
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sorbitol on the Pharmacokinetic Profile of Lamivudine Oral Solution in Adults: An Open‐Label, Randomized Study

Abstract: In children aged ≤4 years, the relative bioavailability of lamivudine oral solution was 37% lower than that of a tablet formulation. An open‐label, four‐way crossover study was conducted in healthy adults to evaluate the effect of sorbitol, a common liquid excipient, on the pharmacokinetics of lamivudine oral solution (ClinicalTrials.gov identifier, NCT02634073). Sixteen subjects were randomized to one of four sequences consisting of four doses of lamivudine 300 mg (10 mg/mL) alone or with sorbitol 3.2, 10.2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Precision and accuracy were evaluated using quality control samples as described by Adkison et al 23 Mass spectrometry was set with multiple reaction monitoring (m/z 233.0 for the internal standard and m/z 230.0 for lamivudine). The initial mobile phase condition of 10:90 (A:B) at 0.65 mL/min was held for 1.7 minutes, adjusted to 50:50 at 1.0 mL/min from 1.8 to 2.8 minutes, held at 10:90 and 0.65 mL/min for 1 minute, and finally returned to 10:90 at 0.65 mL/min (total run time of 4 minutes per sample).…”
Section: Pharmacokinetic Sampling and Bioanalytical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precision and accuracy were evaluated using quality control samples as described by Adkison et al 23 Mass spectrometry was set with multiple reaction monitoring (m/z 233.0 for the internal standard and m/z 230.0 for lamivudine). The initial mobile phase condition of 10:90 (A:B) at 0.65 mL/min was held for 1.7 minutes, adjusted to 50:50 at 1.0 mL/min from 1.8 to 2.8 minutes, held at 10:90 and 0.65 mL/min for 1 minute, and finally returned to 10:90 at 0.65 mL/min (total run time of 4 minutes per sample).…”
Section: Pharmacokinetic Sampling and Bioanalytical Methodsmentioning
confidence: 99%
“…19,20 The majority of lamivudine is renally excreted, with approximately 70% of an administered oral dose eliminated as unchanged drug in urine over 24 hours. 23 Currently, dolutegravir and lamivudine are individually approved in the United States as Tivicay (ViiV Healthcare, Research Triangle Park, North Carolina) and Epivir (ViiV Healthcare), respectively. 19 Metabolism is a minor route of elimination, with only 5% to 10% of the parent drug metabolized to an inactive transsulfoxide metabolite that is excreted in the urine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 14 In a 2012 study, an unexpected interaction was observed between oral solutions of abacavir (ABC) and oral solutions of 3TC, 29 which led to a 2017 study to determine whether sorbitol, an excipient of other antiviral liquid formulations, alters 3TC pharmacokinetics (PK) by altering osmolarity in the intestine, thus reducing the absorption. 30 Maximal concentrations of plasma 3TC were shown to be reduced in a dose-dependent manner as much as 55% when coadministered with sorbitol 13.4 g; plasma 3TC exposure was reduced by 36%–44% in the presence of sorbitol 13.4 g. 30 Decreases in plasma exposure corresponded to increased apparent oral clearance by 57% with sorbitol 13.4 g. Therefore, it is likely that avoiding coadministration of 3TC and sorbitol-containing medicines will be recommended, requiring a switch to tablet regimens.…”
Section: Pharmacologymentioning
confidence: 99%
“…Sorbitol and alcoholic sugars can increase gastrointestinal fluid volume, leading to reduced small intestinal transit time. Consequently, the decreased bioavailability could result in decreased efficacy in certain pediatric age groups, necessitating an increase in dose to match the adult doses, as was the case with the lamuvidine oral solution dosage form, where the dose was increased by 25% . Moreover, development of formulations for oncology indications can present unique challenges in that in many instances the drugs cannot be tested in healthy volunteers due to toxicity issues.…”
Section: Clinical Pharmacology Considerationsmentioning
confidence: 99%